Esperanza e Inevitabilidad en Por 13 Razones. Un análisis de discurso comparado entre las primeras temporadas de la Serie y del documental Beyond the Reasons - Gelado-Marcos, Roberto; Poch-Butler, Santana Lois; Moreno-Felices, Plácido (Fonseca, Journal of Communication, 2020)
The release of 13 Reasons Why in March 2017 attracted not only audiences worldwide, but also a considerable amount of academic attention. A good share of the academic production on the series, though, have focused mostly on its effects. For this reason, and in an attempt to approach the debate from complementary angles, this paper aims at examining the motivations expressed by those involved in the creative process of the show and compared them with the actual discourse in the series’ first season. In order to do that, the methodology triangulates between quantitative and qualitative techniques to approach the research problem from equally complementary angles. The results of these analyses confirm that the creators’ motivation go beyond the mere entertainment, but also inconsistencies between the discourses in Beyond the Reasons and 13 Reasons Why’s first season.